2023
DOI: 10.2196/38713
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Desired Features That Would Be Acceptable and Helpful in a Wrist-Worn Biosensor–Based Alcohol Intervention: Interview Study Among Adults Who Drink Heavily

Abstract: Background Alcohol misuse is highly prevalent in the United States and results in a huge financial and public health burden. Current alcohol reduction treatments are underused, and there is a critical need for innovation in the field. Transdermal alcohol biosensors measure alcohol use passively and continuously and may be helpful tools in alcohol interventions. To date, however, alcohol biosensors have not been widely used to directly intervene on alcohol use. There is a new wrist-worn biosensor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The TAS used in criminal justice sentences, the SCRAM, has been found to result in stigma experienced by wearers ( Richards et al, 2023 , Villalba et al, 2020 ). Our findings revealed that no participant felt uncomfortable wearing the BACtrack Skyn in public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TAS used in criminal justice sentences, the SCRAM, has been found to result in stigma experienced by wearers ( Richards et al, 2023 , Villalba et al, 2020 ). Our findings revealed that no participant felt uncomfortable wearing the BACtrack Skyn in public.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Richards et al (2023) ( Richards et al, 2023 ) interviewed individuals who were interested in reducing their drinking, with some participants having previous experience wearing the SCRAM TAS. Richards et al (2023) found five themes: factors influencing willingness to wear it, personalised messaging of data collected, preference for length of time wearing the biosensor, sharing data collected with others and mental health support. Factors influencing willingness referred to comfort and appearance influencing the willingness to wear the device.…”
Section: Introductionmentioning
confidence: 99%
“…Some harm-reduction interventions may be more suited to utilizing a wearable alcohol sensor to review characteristics of drinking events that result in negative consequences with patients, such as duration of drinking episode or rate of consumption. Research with clinical treatment-seeking and treatment-engaged populations, as well as controlled trials, are needed to determine the impact of the challenges noted here [5], and to identify other challenges within specific interventions or populations [26].…”
Section: Summary/recommendationsmentioning
confidence: 99%